The structural characterisation of HWCVD-deposited nanocrystalline silicon films - Bibhu Swain (South African Journal of Science)
Nanocrystalline silicon (nc-Si) films were deposited by hot-wire chemical vapour deposition (HWCVD) in the presence of varying H2 concentrations and their structural and interfacial character investigated by X-ray diffraction, small-angle X-ray scattering (SAXS) and Raman spectroscopy. The crystalline fraction was around 30 - 50% and the nc-Si crystallite size was in the range 20 - 35 nm. The SAXS results were analysed by Guinier plot, scaling factor, and correlation distance. The nc-Si grains displayed a mass fractal appearance, and the interfacial inhomogeneity distance was ~2 nm.